PERBANDINGAN HUKUM PERSAINGAN USAHA INDONESIA DENGAN SINGAPURA MENGENAI SANKSI LAPORAN KETERLAMBATAN PEMBERITAHUAN MERGER DAN AKUISISI PERUSAHAAN - Kusnady Amirullah (2023)
This research was conducted to explain the comparison of business competition law in Indonesia and Singapore regarding the process and sanctions for reporting late mergers and acquisitions of companies. The main issues in this study are the process of reporting notifications of mergers and acquisitions of companies to business competition institutions and legal comparisons regarding sanctions for reporting late notifications of mergers between Indonesia and Singapore. Mergers and acquisitions are one of the efforts of business actors as a step in advancing their business ventures. The birth of the business competition law is a form of legal certainty for business actors to merge and/or take over company shares. The research conducted here uses normative juridical research methods and it can be concluded that Indonesia's business competition law policy itself adheres to the post-merger notification system or business actors are required to report in writing to the business competition supervisory commission after the merger and/or acquisition of companies no later than 30 days after carrying out these activities. Meanwhile, Singapore adheres to a pre-merger notification system, namely that business actors must consult before conducting a merger and/or acquisition of shares to the competition commission no later than 14 days before carrying out these activities. Furthermore, the comparison of legal sanctions between Indonesia and Singapore is that both apply administrative sanctions with a difference in the amount of the fine.